Madrasah Aliyah Development Through The Concept of Education Quality Assurance - Sandi Kurniawan; Dedi Saputra; Muhammad Adip Fanani; Dewi Ratnasari (al-Afkar, Journal For Islamic Studies, 2024)
This study is a literature study with a descriptive qualitative type, namely library research which seeks to explain the development of Madrasah Aliyah through the concept of education quality assurance. In this study, researchers made use of several references including journals, books, articles and documents related to the theme of this study. This research focuses on the development of educational institutions at the secondary level by paying attention to the concept of quality assurance, especially looking at aspects of educator competence, curriculum, student competence, learning environment, infrastructure and the role of quality assurance in it. The results of the study show that quality assurance and control play an important role in the development of an educational institution, as seen from the improvement in the achievements of the participants in the academic, artistic and sports fields. In addition, activities (PKB) or Continuing Professional Development for educators at Madrasah Aliyah include: First, self-development for Madrasah Aliyah teachers which is carried out in the form of collective teacher activities. Second, teacher scientific publications and third, the innovative works of Madrasah Aliyah teachers which are implemented into simple learning media procurement activities based on ICT.